2013
DOI: 10.4999/uhod.12009
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Erlotinib in Previously Treated Advanced Non-Small Cell Lung Cancer

Abstract: Erlotinib is a potent inhibitor of the epidermal growth factor receptor (EGFR) tyrosine kinase, with single-agent antitumor activity which improves symptom control and quality of life compared with placebo in non-small-cell-lung cancer (NSCLC) patients. We aimed to determine the efficacy and safety of the second, third or fourth-line erlotinib in advanced NSCLC patients in Turkish population. Eighty patients (33 males and 47 females) were retrospectively evaluated. All patients had received a platinum-based re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Therefore, we were able to achieve a 58.9% disease control rate (ORR + SD). Side effects were predictable and manageable, similar to those seen in previous erlotinib clinical trials [8,[11][12][13][14][15]. The median PFS and OS of the study population were 242 and 377 days, respectively, which were similar to those reported in other similar studies [8,[11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Therefore, we were able to achieve a 58.9% disease control rate (ORR + SD). Side effects were predictable and manageable, similar to those seen in previous erlotinib clinical trials [8,[11][12][13][14][15]. The median PFS and OS of the study population were 242 and 377 days, respectively, which were similar to those reported in other similar studies [8,[11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 85%
“…To the best of our knowledge, only two previous studies have investigated the efficacy of this agent in a Turkish population with previously treated advanced NSCLC (Table 3). Karaca et al [11] performed a multicenter retrospective study on the efficacy and safety of erlotinib in 80 advanced NSCLC patients. With an overall disease control rate of 40%, they reported that one patient had achieved CR, 10 patients had PR, and 21 patients had SD [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations